The costs and benefits of Greek EC membership - Heinz-Jurgen Axt (Intereconomics, 1987)
At the time of the southward enlargement of the European Community there were many who doubted whether the new member countries would be able to cope with the strains of accession. It is now a good six years since Greece joined the EC, and the costs and benefits of membership from the viewpoint of the new member countries can be assessed in the light of the Greek experience.
Keywords: 330